The Role of Front Office Staff in Providing Satisfaction and Comfort for Guests at Radisson Golf and Convention Center Batam - Wijaya, Hana; Sukmamedian, Haufi; Lubis, Arina Luthfini; Supardi, Supardi (Akademi Komunitas MAPINDO, 2024)
This study aims to analyze the role and contribution of Front Office staff at Radisson Golf and Convention Center Batam in creating a satisfying and comfortable guest experience. Front Office staff have the main responsibility in direct interaction with guests, such as reception, reservation handling, and check-in and check-out process. The research method used is descriptive method with quantitative and qualitative approaches, through questionnaire survey and in-depth interviews. The sample consisted of randomly selected Front Office employees and hotel guests. The results showed that although the contribution of Front Office employees has not reached the level of statistical significance (p = 0.052), there are positive indications that the improvement of their role has an impact on guest satisfaction. Factors such as communication skills, ability to handle complaints, and efficiency in service greatly influence guests' perception of hotel service quality. In addition, the findings also show that guests' personal preferences and the hotel's environmental conditions also influence the overall guest experience. Based on these findings, hotel management is advised to increase employee training in interpersonal skills and conflict handling, and improve internal communication systems between departments to enhance service coordination. This study provides important insights for hotel management in optimizing the role of the Front Office to improve guest experience.